Multiwavelength optical and NIR variability analysis of the Blazar PKS 0027-426 - Guise, E.; Hönig, S. F.; Almeyda, T.; Horne, K.; Kishimoto, M.; Aguena, M.; Allam, S.; Andrade-Oliveira, F. [UNESP]; Asorey, J.; Banerji, M.; Bertin, E.; Boulderstone, B.; et al. (Oxford University Press (OUP), 2022)
We present multiwavelength spectral and temporal variability analysis of PKS 0027-426 using optical griz observations from Dark Energy Survey between 2013 and 2018 and VEILS Optical Light curves of Extragalactic TransienT Events (VOILETTE) between 2018 and 2019 and near-infrared (NIR) JKs observations from Visible and Infrared Survey Telescope for Astronomy Extragalactic Infrared Legacy Survey (VEILS) between 2017 and 2019. Multiple methods of cross-correlation of each combination of light curve provides measurements of possible lags between optical-optical, optical-NIR, and NIR-NIR emission, for each observation season and for the entire observational period. Inter-band time lag measurements consistently suggest either simultaneous emission or delays between emission regions on time-scales smaller than the cadences of observations. The colour-magnitude relation between each combination of filters was also studied to determine the spectral behaviour of PKS 0027-426. Our results demonstrate complex colour behaviour that changes between bluer when brighter, stable when brighter, and redder when brighter trends over different time-scales and using different combinations of optical filters. Additional analysis of the optical spectra is performed to provide further understanding of this complex spectral behaviour.
Keywords: Galaxies: active; Galaxies: jets; Quasars: individual: PKS 0027-426